Influence of the Ionospheric Delay on Designation of an Aircraft Position - Janusz Cwiklak; Marek Grzegorzewski; Kamil Krasuski (Communications - Scientific letters of the University of Zilina, 2020)
The article presents and describes research results concerning determination of an impact of the ionospheric correction upon the positioning accuracy of an aircraft. The main objective of examinations was to verify three ionospheric models (the Klobuchar model, SBAS model and IONEX model) in determining aircraft coordinates. In the framework of the conducted simulations, the authors determined the aircraft coordinates by means of the SPP code method in the GPS system. The article presents a comparison of the determined aircraft coordinates in the SPP code method in relation to an accurate solution in the RTK-OTF differential technique. Based on the obtained results, it was found that e use of the SBAS and IONEX model is exploited to improve the positioning accuracy of an aircraft in relation to the Klobuchar model, from 20% to 72%, in the geocentric XYZ frame. The obtained findings of a simulation indicate that the ionospheric correction in the SBAS and IONEX models may be used to improve the performance of aircraft coordinates in air navigation.